Psilocin and ketamine microdosing: effects of subchronic intermittent microdoses in the elevated plus-maze in male Wistar rats - Horsley, Rachel R; Páleníček, Tomáš; Kolin, Jan; Valeš, Karel (Behavioural pharmacology, 2018)
Short-term moderate doses of serotonergic and dissociative hallucinogens can be useful in the treatment of anxiety. Recently, a trend has developed for long-term intermittent 'microdosing' (usually one-tenth of a 'full' active dose), with reports of long-lasting relief from anxiety and related disorders; however, there is no scientific evidence for the efficacy of therapeutic microdosing nor to show its lasting effects. The objective of this study was to test for lasting effects on anxiety in rats after microdosing with ketamine or psilocin. Over 6 days, Wistar rats (N=40) were administered ketamine (0.5 or 3 mg/kg), psilocin (0.05 or 0.075 mg/kg), or saline on three occasions. A 5-min elevated plus-maze test was conducted 48 h after the final drug treatment (n=8). Dependent variables were entries (frequency), spent time (%), and distance traveled (cm) in each zone, as well as total frequency of rears, stretch-attend postures, and head dips. Statistical analyses of drug effects used separate independent one-way analysis of variance and pair-wise comparisons using independent t-tests. Statistical effects were modest or borderline and were most consistent with a mildly anxiogenic profile, which was significant at lower doses; however, this conclusion remains tentative. The lower doses of ketamine and psilocin produced comparable effects (to one another) across each variable, as did the higher doses. This pattern of effects may suggest a common (e.g. neurotransmitter/receptor) mechanism. We conclude that microdosing with hallucinogens for therapeutic purposes might be counter-productive; however, more research is needed to confirm our findings and to establish their translational relevance to clinical 'psychedelic' therapy.
Keywords: ketamin; Dose-Response Relationship, Drug; Rats; vztah mezi dávkou a účinkem léčiva; Hallucinogens; antagonisté excitačních aminokyselin; Psilocybin; Time Factors; Rats, Wistar; mužské pohlaví; halucinogeny; Maze Learning; Excitatory Amino Acid Antagonists; krysa rodu Rattus; Locomotion; zvířata; psilocybin; časové faktory; potkani Wistar; Ketamine; lokomoce; bludiště - učení; Male; Animals